Aqueous Extract of Brassica rapa Exerts Antihyperglycemic Activity in Streptozotocin-induced Diabetic Rats - Bouadid, Ismail; Amssayef, Ayoub; Lahrach, Nadia; El-Haidani, Ahmed; Eddouks, Mohamed (Cardiovascular & Haematological Disorders - Drug Targets, 2021)
Aims: The aim of the study was to assess the antihyperglycemic effect of Brassica rapa. Background: Brassica rapa (turnip) is used as an antidiabetic plant. Objective: This work aimed to evaluate the effect of the aqueous extract of Brassica rapa seeds (AEBRS) on glycemia in vivo. Methods: The effect of AEBRS (60 mg/kg) on glycemia and lipid profiles was evaluated. Besides, preliminary phytochemical analysis and the in vitro antioxidant effect were evaluated. Results: AEBRS caused a significant reduction in blood glucose levels in diabetic rats (p<0.0001). In contrast, no significant effect was observed on lipid profiles, whereas antioxidant potential of this extract has been shown. Phytochemical analysis showed the presence of many important phytochemical families. Conclusion: The present study shows that AEBRS has a potent antihyperglycemic ability in diabetic rats.
Keywords: streptozotocin